2018
DOI: 10.1051/e3sconf/20187314015
|View full text |Cite
|
Sign up to set email alerts
|

Digital Media Literacy Campaign in Identifying News

Abstract: This article explains the ways in which a digital media literacy campaign was conducted to help groups of adolescent to identify fake news or hoax and to prevent the further dissemination of fake news. A number of research have shown that young generation, or popularly known as millennials, is the age group of media users that has the highest tendency to read and to spread hoax or fake news. This is also tied to the fact that millennial spend more time on the Internet, and therefore have higher exposure to man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Kultur masyarakat Indonesia memiliki kecenderungan untuk lebih cepat mempercayai sebuah berita tanpa melakukan konfirmasi kebenarannya terlebih dahulu, bahkan terkadang mereka langsung menyebarkannya di media sosial (Juditha 2019). Kampanye literasi media digital membantu meningkatkan kemampuan siswa mengidentifikasi berita palsu atau hoaks dan mencegah penyebaran berita palsu lebih lanjut (Pradekso, Setyabudi, dan Manalu 2018).…”
Section: Pendahuluanunclassified
“…Kultur masyarakat Indonesia memiliki kecenderungan untuk lebih cepat mempercayai sebuah berita tanpa melakukan konfirmasi kebenarannya terlebih dahulu, bahkan terkadang mereka langsung menyebarkannya di media sosial (Juditha 2019). Kampanye literasi media digital membantu meningkatkan kemampuan siswa mengidentifikasi berita palsu atau hoaks dan mencegah penyebaran berita palsu lebih lanjut (Pradekso, Setyabudi, dan Manalu 2018).…”
Section: Pendahuluanunclassified
“…A study conducted by (Pradekso et al, 2018) investigated the effects of digital media literacy campaigns on young people's understanding of fake news or hoaxes. The study found that participants who attended the training had a basic understanding of the terms and meanings of fake news or hoaxes but required assistance in detecting and distinguishing between real news and fake news on social media.…”
Section: Introductionmentioning
confidence: 99%